Bimbingan Kelompok Menggunakan Teknik Diskusi Sebagai Upaya Meningkatkan Pemahaman Siswa Terhadap Pemanfaatan Gadget Di SMP Negeri 1 Wagir - Adrianus Wopa Sil; Eva Kartika Wulan Sari; Laily Tiarani Soejanto (Program Studi Bimbingan dan Konseling, 2026)
Adolescents are the age group with the highest number of social media users, and their use can have both positive and negative impacts on individuals and society (Windari et al., 2021). Gadgets equipped with various applications, such as online games, often attract the attention of children and adolescents, leading them to spend a lot of time playing (Hidayah et al., 2019). The purpose of this study was to determine whether group guidance using discussion techniques could improve students' understanding of gadget use at SMP Negeri 1 Wagir in the 2025/2026 academic year. This study used a quantitative approach with experimental methods. The design used in this study was a pre-experimental, one-group pretest-posttest group design. Based on the results of the scale measurement of understanding of gadget use, 10 students were randomly selected into low, medium, and high categories. The instrument used in this study was a scale instrument for understanding gadget use. The data analysis in this study used the Wilcoxon Signed Rank Test, with the Wilcoxon test statistic showing that Zₕᵢₜᵤₙg was -2.803b (2-tailed) at 0.005. Therefore, the Sig. value (2-tailed) of 0.005 <0.05 can be concluded that providing group guidance services using discussion techniques is effective in improving students' understanding of gadget use at SMP Negeri 1 Wagir. Students are expected to have a better understanding of gadget use and its impact if not improved furthermore, future researchers are expected to develop research using discussion techniques to increase the effectiveness of each step of the discussion technique in group guidance activities.